Correction: "We are pleading for the government to do more": Road user perspectives on the magnitude, contributing factors, and potential solutions to road traffic injuries and deaths in Ghana. - Aldina Mesic; Barclay Stewart; Irene Opoku; Bradley H Wagenaar; Bilal Andoh Mohammed; Sulemana Abdul Matinue; Manal Jmaileh; James Damsere-Derry; Adam Gyedu; Charles Mock; Angela Kitali; Daniel Hardy Wuaku; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300458.].